Hubungan Dukungan Suami dengan Kepatuhan Ibu Hamil dalam Mengonsumsi Tablet Tambah Darah: Relationship Between Husbands' Support and Pregnant Women's Compliance in Consuming Iron Tablets - Sari, Gita Wulanda; Wulandatika, Darmayanti; Ulfa, Siti Maria; Mariani, Hj. (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
The high risk of maternal and neonatal complications due to prenatal anemia is a major public health problem. Iron deficiency is a leading cause, given that pregnant women's iron needs exceed the average and are often not met through daily dietary intake. Pregnant women in Indonesia still neglect the government-provided iron and folic acid. Partner support encourages prenatal health behaviors and is a dominant influencing factor. This study targeted pregnant women in the Alalak Selatan Community Health Center (Puskesmas) area to examine the relationship between partner support and adherence to iron tablet consumption. Thirty pregnant women in their second and third trimesters were randomly selected in a quantitative cross-sectional correlational study. Data were collected through a partner support and iron tablet adherence questionnaire. Spearman's Rho analysis was applied with a significance threshold of 0.05. Results: 80% of respondents reported a lack of partner support, accompanied by non-adherence to iron tablet use. Very strong. A positive relationship was detected between adherence and partner support (p = 0.000; r = 0.667). Compliance with iron tablet consumption was significantly improved among pregnant women with partner support. Partner involvement can enhance the effectiveness and sustainability of prenatal anemia prevention interventions.